Nilai-Nilai Pendidikan Akhlak dalam Keluarga: Kajian QS. al-Taghabun Ayat 14-15 - Salis Irvan Fuadi; Rindi Antika (Matan : Journal of Islam and Muslim Society, 2020)
The purpose of this study is to describe some of the values of moral education in families found in the Koran al-Taghabun verses 14-15. In this verse contained the teachings of moral education both explicitly and explicitly. This research is a literary research, covering searching, reading, and examining writings that are both primary and secondary data sources. The approach used in this paper uses a thematic approach. The results showed that the moral education contained in Surat al-Taghabun verses 14-15 regulates normatively the role of the family family to be able to feel the presence and supervision of Allah anywhere and anytime, so that it creates positive effects such as the child's ability to be honest, trustful, istiqomah, sincere sincere, thank God, and ashamed to do despicable deeds.